Prevalence and risk factors of stress, anxiety and depression among preclinical medical students in Universiti Putra Malaysia in 2014 - D. Fuad, Maher; Munn, Sann Lye; Ibrahim, Normala; Ismail, Siti Irma Fadhilah; Phang, Cheng Kar (International Online Medical Council, 2015)
Aims: To determine the prevalence and risk factors of stress, anxiety, and depression among preclinical medical students of Universiti Putra Malaysia in 2014. Settings and Design: Cross sectional study design was used. Methods and Material: A questionnaire was distributed to the students which included questions about the demographic factors of the students, the DASS-21 questionnaire which is made of three domains namely stress, anxiety and depression and the MSSQ-20 questionnaire which was used to determine the risk factors that affect the students. Statistical Analysis: Data were entered and analyzed using statistical packages for social sciences (SPSS) version 19. Descriptive statistics was used to determine the prevalence of stress, anxiety and depression. Logistic regression was used to determine the risk factors. Results: Prevalence of stress, anxiety, and depression were 16.9%, 52% and 24.4% respectively. Gender, group activities related stressor, love relationship, and absence of financial support are the main risk factors for stress in preclinical medical students of University Putra Malaysia. Multiple logistic regression shows that there is significant association between living in rural area and anxiety [adjusted OR 2.4, 95% C.I. (1.26, 4.59), p= 0.008]. Also, group activities related stressor is significantly associated with anxiety [adjusted OR 2.56, 95% C.I. (1.8, 3.64), p <0.001]. Risk factors for depression include gender (females are protected against depression compared to males [adjusted OR 0.21, 95% C.I (0.095, 6.03), p <0.001]). As in anxiety and stress, group activities related stressor is associated with depression [adjusted OR 3.76, 95% C.I. (2.35, 6.03), P < 0.001]. Conclusions: Group related activity was found to be the main factor affecting psychological distress in preclinical medical students in Universiti Putra Malaysia in 2014.